2019
DOI: 10.1038/s41416-019-0650-z
|View full text |Cite
|
Sign up to set email alerts
|

Reprogramming of fatty acid metabolism in cancer

Abstract: A common feature of cancer cells is their ability to rewire their metabolism to sustain the production of ATP and macromolecules needed for cell growth, division and survival. In particular, the importance of altered fatty acid metabolism in cancer has received renewed interest as, aside their principal role as structural components of the membrane matrix, they are important secondary messengers, and can also serve as fuel sources for energy production. In this review, we will examine the mechanisms through wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
899
1
9

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 1,042 publications
(923 citation statements)
references
References 230 publications
(353 reference statements)
14
899
1
9
Order By: Relevance
“…These 229 genes were manually selected ( Supplementary Table S1) as they are involved in eight central cellular metabolic pathways or processes, of which cellular respiration was then separated into its respective complexes. The number of genes examined from each pathway was as follows: glycolysis, 36 genes (adapted from GO:0061621 and [55]); TCA cycle, 20 genes (adapted from GO:0006099 and [56]); mitochondrial respiratory complex I, 43 genes (adapted from GO:0045333, GO:0046043 and [57]); mitochondrial respiratory complex II, 4 genes (adapted from GO:0045333, GO:0046043 and [58]); mitochondrial respiratory complex III, 9 genes (adapted from GO:0045333, GO:0046043 and [59,60]); mitochondrial respiratory complex IV, 31 genes (adapted from GO:0045333, GO:0046043 and [61]); mitochondrial ATPase, 16 genes (adapted from GO:0046043 and [62]); fatty acid synthesis, 21 genes (adapted from GO:0019368, GO:0046949, GO: 0006629 and [63][64][65][66]); β-oxidation, 18 genes (adapted from GO:0003995, GO:0003985, GO: 0004300 and [67]); glutaminolysis, 7 genes (adapted from GO:0004069, GO:0004352, GO: 0004359, GO: 0004021 and [68]); pentose phosphate pathway, 11 genes (GO:0006098 and [69]); monocarboxylic acid transport (MCT) family, 13 genes (adapted from GO:0008028 and [15]). Boxplot comparisons of gene expression were made with GraphPad Prism v7.0 (Graphpad Software, Inc., San Diego, California, USA).…”
Section: Rna Expression Comparisonsmentioning
confidence: 99%
“…These 229 genes were manually selected ( Supplementary Table S1) as they are involved in eight central cellular metabolic pathways or processes, of which cellular respiration was then separated into its respective complexes. The number of genes examined from each pathway was as follows: glycolysis, 36 genes (adapted from GO:0061621 and [55]); TCA cycle, 20 genes (adapted from GO:0006099 and [56]); mitochondrial respiratory complex I, 43 genes (adapted from GO:0045333, GO:0046043 and [57]); mitochondrial respiratory complex II, 4 genes (adapted from GO:0045333, GO:0046043 and [58]); mitochondrial respiratory complex III, 9 genes (adapted from GO:0045333, GO:0046043 and [59,60]); mitochondrial respiratory complex IV, 31 genes (adapted from GO:0045333, GO:0046043 and [61]); mitochondrial ATPase, 16 genes (adapted from GO:0046043 and [62]); fatty acid synthesis, 21 genes (adapted from GO:0019368, GO:0046949, GO: 0006629 and [63][64][65][66]); β-oxidation, 18 genes (adapted from GO:0003995, GO:0003985, GO: 0004300 and [67]); glutaminolysis, 7 genes (adapted from GO:0004069, GO:0004352, GO: 0004359, GO: 0004021 and [68]); pentose phosphate pathway, 11 genes (GO:0006098 and [69]); monocarboxylic acid transport (MCT) family, 13 genes (adapted from GO:0008028 and [15]). Boxplot comparisons of gene expression were made with GraphPad Prism v7.0 (Graphpad Software, Inc., San Diego, California, USA).…”
Section: Rna Expression Comparisonsmentioning
confidence: 99%
“…These included many members of the integrin pathway, such as Paxillin (−1.9 fold), Vinculin (−1.3 fold) and Talin (−1.2 fold). In addition, we also observed a decrease (−2.3 fold) in mitochondrial trifunctional protein β (Mtp-β), which catalyzes oxidation of long chain fatty acids (46), a possible energy source for tumors (47). We also note a decrease in peptide-treated tumors in proteins such as Chromosome bows (Chb) (−2.16 fold) that are involved in mitotic spindle assembly (48), an effect that could contribute to the observed decrease in cell proliferation of the ISC (Figure 2G-I).…”
Section: Resultsmentioning
confidence: 92%
“…Altered lipid metabolism is being increasingly recognized in aggressive cancers 39 . Cancer cells increase their reliance on de novo biosynthesis and exogenous fatty acid uptake.…”
Section: Discussionmentioning
confidence: 99%
“…SCD is essential for cancer cell survival, and its anti-cancer potential has been reported in multiple cancers 77 . However, not all cancer cells are responsive to SCD inhibition 39 , and a recent study demonstrated FADS2 as an alternative desaturation pathway in SCD-independent cancer cells . Unlike other fatty acids, sapienate is only found in humans and is a major component of human sebum 78 .…”
Section: Discussionmentioning
confidence: 99%